Isotopic biosignatures in carbonate‐rich, cyanobacteria‐dominated microbial mats of the Cariboo Plateau, B.C. Issue 5 (14th August 2013) - Brady, A. L.; Druschel, G.; Leoni, L.; Lim, D. S. S.; Slater, G. F.
Abstract: Photosynthetic activity in carbonate‐rich benthic microbial mats located in saline, alkaline lakes on the Cariboo Plateau, B.C. resulted in p CO2 below equilibrium and δ 13 CDIC values up to +6.0‰ above predicted carbon dioxide (CO2 ) equilibrium values, representing a biosignature of photosynthesis. Mat‐associated δ 13 Ccarb values ranged from 4 to 8‰ within any individual lake, with observations of both enrichments (up to 3.8‰) and depletions (up to 11.6‰) relative to the concurrent dissolved inorganic carbon (DIC). Seasonal and annual variations in δ 13 C values reflected the balance between photosynthetic 13 C‐enrichment and heterotrophic inputs of 13 C‐depleted DIC. Mat microelectrode profiles identified oxic zones where δ 13 Ccarb was within 0.2‰ of surface DIC overlying anoxic zones associated with sulphate reduction where δ 13 Ccarb was depleted by up to 5‰ relative to surface DIC reflecting inputs of 13 C‐depleted DIC. δ 13 C values of sulphate reducing bacteria biomarker phospholipid fatty acids (PLFA) were depleted relative to the bulk organic matter by 4‰, consistent with heterotrophic synthesis, while the majority of PLFA had larger offsets consistent with autotrophy. Mean δ 13 Corg values ranged from −18.7 ± 0.1 to −25.3 ± 1.0‰ with mean Δ 13 Cinorg‐org values ranging from 21.1 to 24.2‰, consistent with non‐CO2 ‐limited photosynthesis, suggesting that Precambrian δ 13 Corg values of −26‰ do not necessitate higher atmospheric CO2 concentrations. Rather, it is likely that the high DIC and carbonate content of these systems provide a non‐limiting carbon source allowing for expression of large photosynthetic offsets, in contrast to the smaller offsets observed in saline, organic‐rich and hot spring microbial mats.